Impact of the Westerly Jet on Rainfall/Runoff in the Source Region of the Yangtze River during the Flood Season - Xin Lai; Yuanfa Gong; Sixian Cen; Hui Tian; Heng Zhang (Advances in Meteorology)
Based on runoff data collected at the Zhimenda station, reanalysis data from the National Centers of Environmental Prediction/National Centers of Atmospheric Research (NCEP/NCAR), and observation data from ground stations in China, this study analyzes the characteristics of changes in runoff in the source region of the Yangtze River (SRYR) during the flood season (from July to September), the relationship between runoff and antecedent rainfall, and the impact of the westerly jet (WJ) on rainfall in the coastal zone of the SRYR. The results show the following. The runoff in the SRYR displays a significant interannual and interdecadal variability. The runoff in the SRYR during the flood season is most closely related to 15-day (June 16 to September 15) antecedent rainfall in the coastal zone of the SRYR. In turn, the antecedent rainfall in the coastal zone of the SRYR is mainly affected by the intensity of the simultaneous WJ over a key region (55–85°E, 45–55°N). When the intensity of the WJ over the key region is greater (less) than normal, the jet position moves northward (southward), and the easterly (westerly) wind anomalies over the region to the west of the SRYR become unfavorable (favorable) to the transport of water vapor from high-latitude regions to the SRYR. In addition, the southerly wind over the equatorial region cannot (can) easily advance northward, which is unfavorable (favorable) to the northward transport of water vapor from the low-latitude ocean. Hence, these conditions result in a decrease (increase) in the water vapor content in the SRYR. Furthermore, the convergence (divergence) anomalies in the upper level and the divergence (convergence) anomalies in the lower level result in the descending (ascending) motion over the SRYR. These factors decrease (increase) the rainfall, thereby decreasing (increasing) the runoff in the SRYR during the flood season.